Peran Multiple Intelligences dalam Pengembangan Keterampilan 6C pada Generasi Z - Soraya, Siti Zazak; Musyahid, Musyahid (Universitas Mathla'ul Anwar Banten, 2025)
This research aims to understand the roles, strategies, impacts, and challenges of implementing multiple intelligences to support the development of 6C skills. The study employed qualitative; with library research, the study was analyzed using content analysis. The research findings indicate that (1) applying multiple intelligences theory in education plays a crucial role in developing 6C skills. (2) Identifying various types of student intelligence through project-based strategies and intelligence mapping can enhance learning effectiveness. (3) The positive impacts of implementing multiple intelligences include increased student engagement, communication skills, and collaboration. (4) However, challenges such as a lack of training for educators and inadequate facilities need to be addressed through collaboration among schools and ongoing training programs.